Conceptual and operational definitions of the components of the nursing diagnosis Acute Pain (00132) - Marisa Dibbern Lopes Correia; Erika Christiane Marocco Duran (Universidade de São Paulo, 2017)
ABSTRACT Objective: to develop the operational and conceptual definitions of the defining characteristics and related factors of the nursing diagnosis Acute Pain (00132) for nonverbal critically ill patients. Method: integrative literature review in the databases/libraries: Medical Literature Analysis and Retrieval System Online (MEDLINE via Pubmed), Cochrane Library, The Cumulative Index to Nursing and Allied Health Literature (CINAHL) and Latin American & Caribbean Health Sciences Literature (LILACS). Results: 799 results were found in the literature, of which 80 studies were selected for full text reading and 16 were used in the elaboration of definitions for the 17 defining characteristics and three related factors of the nursing diagnosis. The gray literature, ie, thesis, dissertations, books, guidelines and dictionary was also explored to ensure the robustness needed to clarify the topics not covered by the studies. Conclusion: the definitions aim to facilitate the identification of the nursing diagnosis for nonverbal critically ill patients and to support future teaching and research on the nursing diagnosis of Acute Pain (00132).